Pemberdayaan Lansia Dengan Storytelling Dan Terapi Kelompok Reminisensi Untuk Mengurangi Risiko Demensia Di Panti Sosial Lanjut Usia - Sulistiyani, Sulistiyani (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Dementia is a common health problem in the elderly and can affect cognitive function, memory, and quality of life. Non-pharmacological interventions such as storytelling and reminiscence group therapy are known to help maintain cognitive function in the elderly. This study aims to analyze the effectiveness of empowering the elderly through storytelling and reminiscence group therapy in reducing the risk of dementia in a nursing home. The study used a quasi-experimental design with a pretest–posttest approach. The study sample consisted of 40 elderly individuals selected using a purposive sampling technique. Cognitive function was measured using the Mini Mental State Examination (MMSE). The results showed a significant increase in the elderly's cognitive scores after participating in the storytelling and reminiscence group therapy program for four weeks. The paired t-test showed a p-value of 0.014 (p < 0.05). It was concluded that empowering the elderly through storytelling and reminiscence group therapy is effective in improving cognitive function and reducing the risk of dementia.